2013
DOI: 10.1007/s12928-013-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of impacted broken balloon by balloon inflation in guiding catheter

Abstract: Broken catheter fragment in a coronary artery during percutaneous coronary angioplasty is a rare complication. It can result in serious problems as a result of thrombus formation and embolization of broken fragment. We report an unusual complication of a broken balloon catheter during angioplasty, which was successfully retrieved by balloon inflation in guiding catheter technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The balloon assembly would minimize the risk for further comorbidities by not localizing the traction to any particular point on the catheter or vascular wall. The balloon technique described here has previously been utilized for retrieving lost stents, primarily in the setting of interventional cardiology procedures (Gupta et al 2005 ; Karaca et al 2016 ; Mehta et al 2014 ). In a prior study, only 2/24 (8.3%) endovascular retrievals were performed using balloon catheters, both of which were used to retrieve broken catheter sheaths.…”
Section: Discussionmentioning
confidence: 99%
“…The balloon assembly would minimize the risk for further comorbidities by not localizing the traction to any particular point on the catheter or vascular wall. The balloon technique described here has previously been utilized for retrieving lost stents, primarily in the setting of interventional cardiology procedures (Gupta et al 2005 ; Karaca et al 2016 ; Mehta et al 2014 ). In a prior study, only 2/24 (8.3%) endovascular retrievals were performed using balloon catheters, both of which were used to retrieve broken catheter sheaths.…”
Section: Discussionmentioning
confidence: 99%
“…A deformed/dislodged stent should be recovered when possible. Various retrieval techniques have been described, including the "balloon inflation technique", use of gooseneck snares, grasping forceps, and stent entrapment with the "twowires" technique or with basket devices [1][2][3][4][5][6][7]. However, all of them are time-consuming and if stent retrieval is not possible, particularly in hemodynamically unstable patients, the easier and faster treatment is to use a new stent to crush the dislodged stent against the vessel wall [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although this technique is not widely accepted for LM and proximal LAD dislodgements because of an increased risk for stent thrombosis and restenosis, this approach was recently reported in a published case report, where a dislodged stent was safely crushed to the distal LM/ostial LAD vascular wall in a hemodynamically unstable patient [8]. In case of failure of all percutaneous techniques and according to the dislodgement coronary site (LM or proximal LAD), surgical intervention may represent the last option [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Mehta V et al [13] reported a successful retrieval of impacted broken balloon by balloon inflation in guiding catheter. Chang WT et al [14] also described two similar cases of successful percutaneous retrieval of ruptured coronary balloon during emergency or elective PCI.…”
Section: Discussionmentioning
confidence: 99%